Peran Generasi Z dalam Moderasi Beragama di Era Digital - Helminia Salsabila; Devi Sintya Yuliastuty; Nur Halimah Silviatus Zahra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article discusses the role of generation Z in religious moderation in the digital era. Generation Z is the generation born between 1995-2010. Generation Z which is seen as the educated generation in the current era of digitalization which is expected to support the implementation of religious moderation policies or programs. This research is a type of descriptive qualitative research and uses literature research methods. The results of this study indicate that religious moderation is a way of practicing religious life by taking the middle way or how to avoid extreme actions or fanaticism. In other languages, moderation can be understood as a process of actualizing religious teachings in a fair, balanced and wise manner. Religious moderation is something that the people of Indonesia really need to avoid the threats of extremist and liberal groups who only want division. Generation Z's role is needed in supporting religious moderation, including social control on social media, being moderate or not too fanatical, being a good people, spreading the importance of religious moderation and inviting kindness. Artikel ini membahas tentang peran generasi Z dalam moderasi beragama di era digital. Generasi Z adalah generasi yang terlahir antara tahun 1995-2010. Generasi Z yang dipandang sebagai generasi terpelajar di era digitalisasi saat ini diharapkan mendukung terlaksananya kebijakan atau program moderasi beragama. Penelitian ini adalah jenis penelitian kualitatif deskriptif dan menggunakan metode penelitian studi Pustaka. Hasil penelitian menunjukkan bahwa moderasi beragama adalah cara mengamalkan kehidupan beragama dengan mengambil jalan tengah atau cara diri menghindar dari tindakan ekstrim atau fanatisme. Bahasa lainnya, moderasi dapat dipahami sebagai suatu proses pengaktualisasian ajaran agama secara adil, seimbang, dan bijaksana. Moderasi beragama menjadi suatu hal yang sangat dibutuhkan oleh masyarakat Indonesia untuk menghindarkan diri dari ancaman kelompok ekstrimisme dan liberalisme yang hanya menginginkan perpecahan. Diperlukan peran generasi Z dalam mendukung moderasi beragama antara lain yaitu sebagai kontrol sosial dalam media sosial, bersikap pertengahan atau tidak terlalu fanatik, menjadi umat yang baik, menyebarkan tentang pentingnya moderasi beragama dan mengajak dalam hal kebaikan.